DESTRUCTION OF CULTURAL HERITAGE AS A FORM OF CULTURAL AGGRESSION IN WARS - Aliyeva, Yegana (Collection of scientific papers «ΛΌГOΣ», 2025)
The destruction of cultural heritage during armed conflicts has been a persistent and disturbing feature of human history, often serving as a tool of cultural aggression. Throughout centuries, cultural sites, monuments, and artifacts have been targeted in wars as part of strategies aimed at undermining the identity, memory, and spirit of affected communities. From ancient civilizations to modern conflicts, cultural heritage has repeatedly been destroyed with the intent to erase historical continuity, break national identity, and dominate the enemy. The deliberate targeting of cultural heritage sites has increasingly come to be recognized as a form of warfare that extends beyond physical and territorial conquest, aiming to alter the cultural fabric of a society.